El uso de las TIC en la educación universitaria: motivación que incide en su uso y frecuencia - Abarca Amador, Yohanna (2015)
This study seeks anwers to the following research questions: What motives teachers to use technological tools such as wikis, forums, and blogs? Which technological tools do teachers use at college level most frequently? To obtain the anwers, a two-stage mixed method was used in a sequential way with data triangulation. The instruments used for this triangulation were a questionnaire (quantitative method) and an interview (qualitative method). The results obtained showed that teachers use technological tools more frequently when they have theoretical knowledge and the necessary technological skills to use information technologies (IT) effectively. The results of this study also suggest that teachers not only show a positive attitude towards the use of IT, but are also aware of their importance in the future development of the students as competent professionals.